2020
DOI: 10.3389/fphar.2020.00118
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Mechanisms of Hawthorn and Its Extracts on Atherosclerosis: A Review

Abstract: Cardiovascular disease (CVD), especially atherosclerosis, is a leading cause of morbidity and mortality globally; it causes a considerable burden on families and caregivers and results in significant financial costs being incurred. Hawthorn has an extensive history of medical use in many countries. In China, the use of hawthorn for the treatment of CVD dates to 659 AD. In addition, according to the theory of traditional Chinese medicine, it acts on tonifying the spleen to promote digestion and activate blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 97 publications
0
34
0
Order By: Relevance
“…In Europe and Eastern Asia, the genus Crataegus (Hawthorn berry) has been therapeutically applied for heart disease treatment [22,25], digestive support [30], blood circulation improvement [21,25], and pain relief [28]. Several studies have pointed out other pharmacological effects of hawthorn species on oxidative stress and the immune system, along with explanations of the molecular mechanism underlying these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe and Eastern Asia, the genus Crataegus (Hawthorn berry) has been therapeutically applied for heart disease treatment [22,25], digestive support [30], blood circulation improvement [21,25], and pain relief [28]. Several studies have pointed out other pharmacological effects of hawthorn species on oxidative stress and the immune system, along with explanations of the molecular mechanism underlying these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Crataegus laevigata , also known as midland hawthorn, belongs to the family Rosaceae, being widely distributed in western and central Europe, and is well-known for its pharmacological effect on cardiovascular disease [ 21 , 22 , 23 , 24 , 25 ]. The phytoactive secondary compounds dominantly present in hawthorn fruits are proanthocyanidins (polymers of (epi)catechin units) [ 26 , 27 ] and flavonoids [ 28 ], which have been investigated for various pharmacological effects, especially anti-inflammation [ 25 , 28 , 29 , 30 ]. Nevertheless, contrary to the well-investigated cardiovascular effects, data about other pharmacological activities of C. laevigata extracts, particularly those on anti-inflammatory effects on skin diseases, have been poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells are highly sensitive to stimuli and physiological cues in the immediate environment (33). Thus, injury of the vascular endothelium is an initial step in the pathogenesis of vascular remodeling and contributes to vascular remodeling as a source of SM-like cells, as endothelial cells can acquire a fibro-proliferative mesenchymal phenotype through EndMT under specific pathological conditions, including shear stress, oxidative stress and atherosclerosis (34). The present study demonstrated that endothelial cells differentiate towards a SM-like phenotype via EndMT trans-differentiation when treated with TGF-β1, and that the KLF4 signaling pathway was involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated above, many beneficial properties have been attributed to hawthorn, including anticancer [55], anti-HIV, anti-diabetic [56], and anticoagulant activity [57], cardioprotective effects [58][59][60][61][62][63][64][65], hepatoprotective effects, antihyperglycemic and antihyperlipidemic activities, wound healing effects [66], antimicrobial effects, gastroprotective effects, treatment of metabolic syndrome [67], regulation of cholesterol homeostasis [68], anti-atherosclerosis effects [69][70][71][72], anti-aging effects [73], ischemia protective effects [74], treatment of cognitive disorders, neuroprotective effects, regulating gastrointestinal motility [75], anti-inflammatory activities [76,77], regulation of the gut-brain axis [78], treatment of hypertension [79], antioxidant activity [80][81][82][83][84][85], anti-hypoxic activities [86], antidepressant effects [87], anti-Alzheimer's effects, and treatment of intestinal microbial disorder [88].…”
Section: In Vitro and In Vivo Therapeutic Potentials Of Hawthorn: An mentioning
confidence: 99%